Identifying aspects of temporal orientation in students' moral reflections. Issue 2 (20th October 2020) - Ammert, Niklas; Sharp, Heather; Löfström, Jan; Edling, Silvia
Abstract : page_132 other History education comprises moral issues and moral aspects, often perceived as an important and meaning-making foundation that makes learning relevant and interesting. The interrelationship between time layers fuels historical interpretations and facilitates perceptions of moral issues. This article focuses on a study investigating how secondary school students express inter-temporal relationships in encounters with a morally challenging historical event, which for the participants would have been a moral dilemma. Using historical consciousness as the theoretical framework, a matrix linking two prominent theoretical models – Jörn Rüsen's (2004) types of narratives and Ann Chinnery's (2013) strands of historical consciousness – was developed to analyse and categorize secondary school students' expressions of temporal orientation. To carry out the research, 15-year-old Finnish and Swedish students read an excerpt from Christopher Browning's (2017) book Ordinary Men: Reserve Police Battalion 101 and the Final Solution in Poland (originally published in 1992). The students answered and discussed open-ended questions regarding the relevance of the text to their lives and others' lives, and the applicability of this historical situation to Europe now and in the future. Using this empirical material, the analysis provides a tentative overarching depiction of students' expressions of temporal orientation, and reports on findings of how temporal orientations relate to moral reflection.